Characteristics, Phytochemical Analysis and Biological Activities of Extracts from Tunisian Chetoui Olea europaea Variety - Ines Khlif; Karim Jellali; Thomas Michel; Maria Halabalaki; Alexios Leandros Skaltsounis; Noureddine Allouche (Journal of Chemistry)
This study selected 10 extracts from Tunisian chetoui O. europaea variety for their total phenolics, flavonoids, and phytochemical analyses as well as for their antioxidant and antimicrobial activities determination. The in vitro antioxidant property was investigated using DPPH, ferric reducing antioxidant capacity (FRAP), oxygen reducing antioxidant capacity (ORAC), and β-carotene-linoleic acid bleaching assays while antimicrobial activity was evaluated using macrodilutions method. For all organs of chetoui O. europaea variety, the investigated activities were found to be higher in the polar extracts (ethyl acetate, methanol, and methanol/water). These activities were correlated with the presence of phenolic compounds. Phytochemical analyses revealed that the crude extracts contain triterpenoids, quinones, and flavonoids. High performance liquid chromatography (HPLC) and high performance thin layer chromatography (HPTLC) confirmed the presence of phenolic compounds in the studied extracts.